2019
DOI: 10.1111/ene.14070
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the effect of uric acid on striatal dopamine in early Parkinson's disease

Abstract: Background and purposeHigh uric acid (UA) levels have been shown to exert a neuroprotective effect in Parkinson's disease (PD) by inhibiting oxidative stress in the nigrostriatal pathway. However, the association between striatal dopamine activity and UA level has not been clarified.MethodsA total of 213 patients with early PD were enrolled. All patients underwent positron emission tomography using 18F‐N‐(3‐fluoropropyl)‐2beta‐carbon ethoxy‐3beta‐(4‐iodophenyl) nortropane and a venous blood test for quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…That UA has a protective effect is further indicated by the positive correlation with age of onset, supporting recent findings (Oh et al 2019) that higher concentrations may delay the degenerative process and hence the emergence of symptoms. That this was only identified in the subjects who were not agricultural workers is notable; it may reflect the effect of a UA threshold which is not reached in most agricultural workers with further reduced UA concentrations, or it may indicate that other factors, such as pesticide exposure, are more important in determining risk of PD in this group.…”
Section: Discussionsupporting
confidence: 84%
“…That UA has a protective effect is further indicated by the positive correlation with age of onset, supporting recent findings (Oh et al 2019) that higher concentrations may delay the degenerative process and hence the emergence of symptoms. That this was only identified in the subjects who were not agricultural workers is notable; it may reflect the effect of a UA threshold which is not reached in most agricultural workers with further reduced UA concentrations, or it may indicate that other factors, such as pesticide exposure, are more important in determining risk of PD in this group.…”
Section: Discussionsupporting
confidence: 84%
“…Our results show that hyperuricemia is a sign of good nutrition, and the reasons may be as follows. Research shows that oxidative stress is a leading factor in the pathogenesis of idiopathic PD, and two intrinsic antioxidative molecules, i.e., bilirubin and UA, are known to protect dopaminergic neurons from oxidative stress in PD (22). Another study showed that the higher UA level group in female PD patients showed a smaller reduction in dopamine transporter uptake in the posterior putamen (23).…”
Section: Discussionmentioning
confidence: 99%
“…These measures are necessary because limiting social contact of affected people was crucial for the control of COVID-19, as asymptomatic or mildly symptomatic patients can spread the virus [16]. Subsequently, the decision to update the case definition of infection has shown an increase in new positive cases after the onset of the disease in people with no notion of travel (Figure 1) [17,18] and (Figure 2) [17]. This update has taken into consideration the evolution of the national epidemiological situation of COVID-19, marked by the emergence of the disease in some people with no notion of travel.…”
Section: The World Health Organization (Who) Declared a Globalmentioning
confidence: 99%
“…In addition, as of 9 April, the percentage of cases not yet recovered is estimated at 85%. (Figure 4) [17,18] and (Figure 5) [17].…”
Section: The World Health Organization (Who) Declared a Globalmentioning
confidence: 99%
See 1 more Smart Citation